Drivers for ecosystem respiration during the drawdown period in Dongting Lake, China - Zhou, Yan; Jing, Lei; Wang, Shaoquan; Jia, Yifei; Wang, Yushu; Lei, Guangchun (Frontiers in Environmental Science, 2023)
Global lakes play an active role in releasing carbon into the atmosphere. However, previous research was less focused on shallow tropical and sub-tropical lakes, especially ecosystem respiration during the drawdown period. This study was designed to determine the environmental factors that determine ecosystem respiration during the drawdown period in a typical shallow sub-tropical lake, Dongting Lake in China. Ecosystem respiration from the exposed mudflat and a newly colonized meadow were investigated using a Li-8100 soil CO2 flux system in situ. The soil water content soil organic carbon (SOC), dissolved organic carbon (DOC), total nitrogen and soil C/N ratio were measured at 0–30 cm soil depth layers. No difference was found among different soil depth layers for soil properties, while the dissolved organic carbon value varied significantly among different levels of the cumulative days of the mudflat exposed to the air (CDE). Carex colonizing significantly increased soil organic carbon and DOC at the surface soil layer. Exposure to the air and Carex colonizing together strengthened the intensity of carbon dioxide (CO2) emission in the mudflat, achieving 0.716 ± 0.114 μmol m-2s-1 and 2.240 ± 0.375 μmol m-2s-1, respectively. Exposure to the air led mudflat to exceed other landscapes or different vegetation types in Dongting Lake, becoming the most active area releasing CO2 into the atmosphere, with the respiration flux reaching a peak period at around 60 days after exposure, which was enormously reinforced by Carex colonizing. Reducing the area and duration of mudflat exposure to the air during the drawdown period might be useful in reducing CO2 emissions to the atmosphere in shallow sub-tropical lakes.